Learning and Mechanism Design: An Experimental Test of School Matching Mechanisms with Intergenerational Advice. - Ding, Tingting; Schotter, Andrew (Economic Journal, 2019)
While the mechanisms that economists design are typically static, one-shot games, in the real world, mechanisms are used repeatedly by generations of agents who engage in them for a short period of time and then pass on advice to their successors. Hence, behaviour evolves via social learning and may diverge dramatically from that envisioned by the designer. We demonstrate that this is true of school matching mechanisms—even those for which truth-telling is a dominant strategy. Our results indicate that experience with an incentive-compatible mechanism may not foster truthful revelation if that experience is achieved via social learning.